MEASURING STUDENT INTEREST IN THE INDUSTRIAL REVOLUTION 4.0 THROUGH RASCH ANALYSIS - Astuti, Diana; Mudjiran, Mudjiran; Alizamar, Alizamar (International Journal of Research in Counseling and Education, 2020)
Interest in learning can help students in learning activities and get satisfying results. The phenomenon that occurs is the low student learning outcomes because of a lack of interest in learning possessed by students. This study measures student interest in the vocational high school (SMK) learning. This study involved 154 students. The instrument in the study was in the form of a learning interest questionnaire with a Likert model scale. Data were analyzed using the Rasch Model approach. The results showed that the learning interest of some students was in the medium category. In addition, there were 30 students who provided answers or showed outliers. As for the quality of the learning interest instrument used, it is good to be used to identify student interest in learning, we can see this from the reliability value of 0.97. The findings show that overall student interest in learning is in the medium category.